The role of outdoor seating facilities for the elderly in dense settlements at Ngampilan Village, Yogyakarta (ARTEKS : Jurnal Teknik Arsitektur, 2021)
The environmental amenities of areas with a high elderly population need to be adjusted to support their lives and ensure they experience a healthy aging process. Therefore, this research examines the role of residential areas in providing support to the daily activities of the elderly for their optimal and everyday use of available outdoor seating facilities. Data were obtained from 25 outdoor seating facilities in a densely populated environment in Yogyakarta City center through observations, interviews, and person-centered mapping of the elderly as respondents. The results showed that the elderly utilize outdoor seating for social, recreation, rest, shelter, and household activities. Therefore, it is still necessary to improve the physical quality of seating in these facilities to ensure that they are maximally utilized by the elderly. The important aspect in establishing these criteria are as follows: (1) dimensions, (2) protection, (3) material, (4) Form, and (5) comfort.
Keywords: Elderly; Outdoor space; Residential environment; Seating facilities